Synthesis of surface-modified TREN-cored PAMAM dendrimers and their effects on the solubility of sulfamethoxazole (SMZ) as an analog antibiotic drug - Gurbuz, Mustafa Ulvi; Erturk, Ali Serol; Tulu, Metin (TAYLOR & FRANCIS LTD, 2017)
Sulfamethoxazole (SMZ) is a sulfonamide and used widely in the treatment of bacteriostatic and urinary tract infections with trimethoprim as an antibiotic. The problem with SMZ is its poor water solubility, therefore, low bioavailability in clinical applications. In this study, we synthesized new-generation Tris(2-aminoethyl)amine (TREN)-cored amine (NH2),Tris(hydroxymethyl)aminomethane (TRIS), and carboxyl (COOH) terminated different generations T2-T4 poly(amidoamine) PAMAM dendrimers. Synthesized PAMAMs were characterized by H-1 NMR, C-13 NMR, ATR-FTIR, spectroscopic titrations, and evaluated as potential solubility enhancers and drug carriers of sulfonamides by taking SMZ as a model drug. The effect of concentration, generation, and surface groups of PAMAMs on the solubility of SMZ was also investigated. Results showed that the solubility of SMZ improved significantly with an increasing generation size (T2-T4) and PAMAM dendrimer concentration (0-2 mM). The role of PAMAMs in the solubility enhancement of SMZ was in the order of T4.NH2 > T4.COOH > T3.NH2 > T4.TRIS > T2.NH2 > T3.COOH > T3.TRIS > T2.COOH > T2.TRIS, and in the ranges of 5- to 45-fold with maximum SMZ loading 7 to 61 mole/mole per PAMAM dendrimer molecule. In vitro release studies demonstrated that SMZ-PAMAM dendrimer complexes at the end of 2-h drug release (16-26%) was considerable slower than pure SMZ (38.8%).
Keywords: Dendrimers; poly(amido-amine) PAMAM dendrimer; drug carrier; sulfamethoxazole; MICROWAVE-ASSISTED SYNTHESIS; POLY(AMIDOAMINE) DENDRIMERS; PHARMACEUTICAL APPLICATIONS; IN-VITRO; DELIVERY; COMPLEXATION; PH; ENHANCEMENT; DISSOLUTION; CARRIERS; Pharmacology & Pharmacy